Poor youth, violence and citizenship - Lopes, Roseli Esquerdo (2008)
This article searches, from a social historical point of view, for ways of facing the violence that afflicts teenagers and youngsters of urban popular groups in Brazil. Violence is a complex phenomenon of great importance in many social substrates. The vulnerability of those teenagers and youngsters, as shown by a plurality of indexes, has reached unacceptable highs in Brazil, where the public policies, so far, have proven to be inadequate, insufficient and fragmented. Thus, the article reports and analyzes a social intervention based on education and on the defense of human rights deriving from citizenship, targeted on socially vulnerable teenagers and youngsters, specifically those living in a deprived region lacking basic social infrastructure located in a medium-sized town in the state of São Paulo. Different projects dealt with actions based on an interdisciplinary approach, according to the following aspects: a) School violence; b) Urban violence; c) Human rights violation and violence in the community. The results showed a collective frame related to actions concerning teenagers and youngsters of urban popular groups and their alternatives. Strategies for dealing with these matters in public spaces are formulated, from regular schools to more recent institutions concerning the contradictory logic of social rights. Therefore, subsidies are provided for public policies in order to reduce the differences, discrimination and violence that afflict teenagers and youngsters in Brazil.